Clinical description of gestation process course in women with miscarriage - V. A. Plotnik (Zaporožskij Medicinskij Žurnal)
The features of clinical course of pregnancy in women with miscarriage are studied. Anamnestic peculiarities are defined, which in combination with risk factors lead to miscarriage. This may allow to predict the risk of miscarriage and to apply preventive measures.